Development of Temperature and Heat Teaching Modules Based on Problem Based Learning to Improve Students' Critical Thinking - Mutiara Putri; Hamdi Akhsan; Kistiono (Universitas Negeri Yogyakarta, 2026)
This study aims to develop a physics teaching module based on Problem-Based Learning (PBL) on Temperature and Heat for 11th grade high school students, integrated with deep learning principles and PhET virtual practicums, to enhance critical thinking skills. Due to time and resource constraints, only the first three phases of the 4-D model (Define, Design, Develop) were implemented. Three experts in content, media/design, and curriculumvalidated the module. Ten Grade 11 students from SMA PGRI Gelumbang participated in a small-group trial to assess practicality. Data were collected using a Likert-scale questionnaire and analyzed with the HEOS % formula. The module achieved an average validity score of 96.58%, classified as Very Valid, confirming alignment with curriculum standards and scientific accuracy. Practicality scores ranged from 83% to 90%, falling in the Practical to Very Practical category, indicating students found the module engaging, understandable, and feasible within classroom constraints. The integration of PhET simulations significantly reduced barriers to understanding abstract concepts like heat capacity and energy transfer. The module’s structure supports student-centered learning and can be adapted to diverse learning contexts. By embedding contextualized problems and deep learning strategies, it effectively fosters conceptual understanding and higher-order thinking. The high validity and practicality scores collectively demonstrate that the PBL-integrated module is both technically robust and pedagogically effective for improving critical thinking in thermal physics education. Keywords: Problem based learning, deep learning, temperature and heat, PhET virtual labs, 4-D model, critical thinking.